Implementasi Entrepreneurial Marketing dalam Mempertahankan Usaha Mikro, Kecil, dan Menengah pada Usaha Bakulanvia di Masa Pandemi - Rahmanisa, Rahmanisa; Sitorus, Onny Fitriana (Jurnal Maksipreneur, 2023)
The Creative Economy Agency noted that in 2020 around 60% of MSMEs in the culinary sector in Indonesia were affected by the Covid-19 pandemic which made the wheels of the business economy temporarily stop. On the other hand, some MSMEs can still survive and rise ready to live the new normal even though they have been hit by a pandemic. The purpose of this study is to find out how the implementation of Entrepreneurial Marketing in maintaining Micro, Small, and Medium Enterprises (MSMEs) during the pandemic. This research uses a descriptive qualitative approach.  The data source was taken using purposive sampling techniques.  Data collection uses active participative observation techniques, semi-structured interviews, and document studies. Data validation using source triangulation and techniques.  Data analysis techniques are carried out using the constant comparative method. The results showed that Bakulanvia business people implemented entrepreneurial marketing which was reviewed through an opportunity focused on the implementation of joining Jakpreneur and expanding relationships. Innovation-oriented is by innovating attractive packaging different from others. Value Creation is through satisfaction and customer input suggestions that are constructive. Calculated risk-taking is by making strategies through promos and utilizing social media. Research limitations and suggestions for subsequent research are provided.